PENGARUH MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR SISWA DI SMP NEGERI 2 TABUKAN UTARA - Priscicilia A. D. Karaeng; Djeli A. Tulandi; Marianus (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2022)
The Discovery Learning model is a series of learning activities that maximally involve all students' abilities to search and investigate systematically, critically, and logically. so, they can find their own knowledge, attitudes, and skills as a form of behavior change. The purpose of this study was to determine the effect of the Discovery Learning Model on Student Learning Outcomes at SMP Negeri 2 Tabukan Utara. The method used in this research is pre-experiment using one group pretest-posttest design. The sample of this research is the students of class VIII, totaling 16 people. The results of the Paired Sample Test analysis with the help of the SPSS program, it is known that the significant value is 0.000, this means less than 0.05, then H0 is rejected and Ha is accepted. These results indicate that there is an average difference between pre-test and post-test learning outcomes, which means that there is an effect of using the Discovery Learning model on student learning outcomes.